2008
DOI: 10.1128/jcm.00835-08
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in a South American Population: Dynamic Spread of Class 1 Integrons and Multidrug Resistance by Homologous and Site-Specific Recombination

Abstract: One hundred four bacterial strains mediating urinary tract infections in separate individuals from a Uruguayan community were isolated. Forty-six strains conferred a multidrug resistance phenotype. All 104 strains were examined for the presence of class 1, 2, and 3 integrons. Class 1 integrons were found in 21 isolates across four distinct bacterial genera. A large class 1 integron in a Klebsiella pneumoniae strain was fully sequenced and was 29,093 bp in length. This integron probably arose by homologous reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 46 publications
4
43
2
Order By: Relevance
“…Four prawns, harvested from each of 16 distinct locations from Australia, the South Pacific, and Southeast Asia, were examined. More than 75% of mixed cultures from individual prawns tested positive for class 1 integrons with use of the primers HS915 and HS916 (15). PCR with these primers on pure isolates derived from such mixed cultures revealed that about 3% of 850 colonies were positive for a class 1 integron, a number consistent with findings of other studies (10,25).…”
supporting
confidence: 85%
“…Four prawns, harvested from each of 16 distinct locations from Australia, the South Pacific, and Southeast Asia, were examined. More than 75% of mixed cultures from individual prawns tested positive for class 1 integrons with use of the primers HS915 and HS916 (15). PCR with these primers on pure isolates derived from such mixed cultures revealed that about 3% of 850 colonies were positive for a class 1 integron, a number consistent with findings of other studies (10,25).…”
supporting
confidence: 85%
“…A mosaic sequence comprising ISKpn12, ISKpn11, aacC2, and a Tn2 transposon was located upstream of dbp. This region was highly homologous to a sequence carried by K. pneumoniae 12836 (15). The IRtnp repeat of Tn2 was adjacent to the remaining part of strB (strB*2).…”
Section: Vol 55 2011mentioning
confidence: 95%
“…All the six isolates with the plasmids weight of 854bp were also resistance to cloxacillin, amoxicillin, ampicillin and cotrimoxazole. The emergence of R-plasmids in this study could be ascribed to the indiscriminate and widespread use of antibiotics caused by over-the-counter availability of antibiotics as well as the higher exposure of people to enteric flora in places with poor sanitation 25,39,55,56 . Clinical isolates of E. coli which showed multiple drug resistance were also found to harbour plasmids with molecular sizes ranging from 2kb to 6.5 kb and a maximum 26kb.…”
mentioning
confidence: 86%